Impact of ‘Internet + dietary diary management’ on serum TP, ALB, PA levels and nutritional risk for elderly patients with esophageal cancer - Yue Fu; Qingmiao Zhu; Chang Liu; Qi Li; Nuoxiaoxuan Wang; Ning Zhao (Experimental Gerontology)
Objective: This study examines the impact of “Internet + diet diary management” on serum total protein (TP), albumin (ALB), and prealbumin (PA) levels, as well as nutritional risk during the postoperative home care period for elderly esophageal cancer patients. Methods: From May 2022 to May 2023, 74 elderly patients who underwent surgical treatment and were discharged as planned were included. Patients were assigned into a control group and a research group, with 37 in each, using a digital randomization table. Both groups received continuous nursing care, with the research group receiving additional “Internet + diet diary management” during their ongoing care. Serum levels of TP, ALB, and PA, along with other nutritional indicators and scores from the Patient-Generated Subjective Global Assessment (PG-SGA), were compared preoperatively and one month post-discharge. Results: Preoperatively, there was no significant difference in serum indicators and PG-SGA scores between the two groups (P > 0.05). One month postoperatively, the research group showed higher levels of serum ALB, TP, PA, IgA, and IgG, and lower PG-SGA scores than the control group (P < 0.05); no significant differences were found in serum levels of IgM, CA19–9, CA72–4, cyfra21–1, NSE, SCC, and CEA between the groups (P > 0.05). Conclusion: The application of “Internet + diet diary management” can improve the nutritional status and reduce nutritional risk during the postoperative home care period for elderly patients with esophageal cancer.